Perbandingan Sistem Levitasi Magnetik Ems dan Eds Untuk Maglev Indonesia - Muhammad Akhdan Fadhil; Erzi Agson Gani; Ade Bagdja; Gita Amperiawan; Sovian Aritonang (Syntax Corporation Indonesia, 2024)
Maglev trains are considered for urban transport and intercity transport systems. On low-medium speed Maglev trains, the operating routine is shorter than that of high-speed trains. Therefore, EMS and LIM technologies are preferred from the point of view of construction costs. However, in high-speed operation, EDS and NGO technologies are preferred for handling, and reliability. In addition, as the development of high-temperature superconductors and new types of permanent magnets develop, stronger and more cost-effective magnetic energy will be used for Maglev trains. The authors believe this technology can be utilized not only for railway applications but also aircraft launch systems and spacecraft launch systems. The need for a new and improved transportation system prompted many countries to be interested and seek to develop Maglev railways. However, although Maglev trains have been studied and developed for approximately half a century, few countries have the knowledge and expertise to do so. This review paper attempts to describe the current complete system in detail and summarizes the basic core technologies of Maglev trains from an electrical engineering point of view. The research hopes to be useful for people interested in this to assimilate Maglev train technology including magnetic levitation, propulsion, guidance, and power supply systems.